The determinants of supplier selection criteria at Alcatel-Lucent / Nor Ilyani Asgarali - Asgarali, Nor Ilyani (Faculty of Business and Management, 2011)
Supplier selection is the process by which firms identify, evaluate, and contract with supplier. With increasingly competitive global world markets, companies are under intense pressure to find ways to cut production and material costs to survive and sustain their competitive position in their respective markets. Since a qualified supplier is a key element and a good resource for a buyer in reducing such costs, evaluation and selection of the potential suppliers has become an important component of supply chain management. This case study analyzes the main criteria of potential supplier of Alcatel-Lucent Malaysia Sdn Bhd. Those criteria are quality, delivery performance and cost. The case study first will identify as many as possible factor for each element, then the researcher will select the major factor foreach elements and conduct research to support each factor.